2011
DOI: 10.1007/s10059-011-0046-2
|View full text |Cite
|
Sign up to set email alerts
|

Root Hair-Specific EXPANSIN A7 Is Required for Root Hair Elongation in Arabidopsis

Abstract: Expansins are non-hydrolytic cell wall-loosening proteins that are involved in the cell wall modifications that underlie many plant developmental processes. Root hair growth requires the accumulation of cell wall materials and dynamic cell wall modification at the tip region. Although several lines of indirect evidence support the idea that expansin-mediated wall modification occurs during root hair growth, the involvement of these proteins remains to be demonstrated in vivo. In this study, we used RNA interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 19 publications
6
72
0
1
Order By: Relevance
“…In Arabidopsis, two members of the expansin family of cell wall proteins, EXPANSIN A7 (EXPA7: At1g12560) and EXPANSIN A18 (EXPA18: At1g62980), exhibit root-hair-specific expression (Cho and Cosgrove, 2002;Jones et al, 2006;Won et al, 2009;Bruex et al, 2012), and altering their levels by treatment with exogenous protein preparations or by RNAi-based suppression, resulted in altered root hair tip growth (Cosgrove et al, 2002;Lin et al, 2011). Many hydroxyproline-rich glycoproteins (HRGPs) are found in cell walls (Velasquez et al, 2011;Mohnen and Tierney, 2011).…”
Section: Root Hair Cell Wallsmentioning
confidence: 99%
“…In Arabidopsis, two members of the expansin family of cell wall proteins, EXPANSIN A7 (EXPA7: At1g12560) and EXPANSIN A18 (EXPA18: At1g62980), exhibit root-hair-specific expression (Cho and Cosgrove, 2002;Jones et al, 2006;Won et al, 2009;Bruex et al, 2012), and altering their levels by treatment with exogenous protein preparations or by RNAi-based suppression, resulted in altered root hair tip growth (Cosgrove et al, 2002;Lin et al, 2011). Many hydroxyproline-rich glycoproteins (HRGPs) are found in cell walls (Velasquez et al, 2011;Mohnen and Tierney, 2011).…”
Section: Root Hair Cell Wallsmentioning
confidence: 99%
“…Because EXPA7 is required for normal root hair growth in Arabidopsis (Lin et al, 2011) and its orthologs are well conserved throughout angiosperms (Kim et al, 2006), we presumed that root hair-specific orthologs of EXPA7 are involved in root hair growth in S. moellendorffii. A phylogenetic analysis showed that the S. moellendorffii genome includes two EXPAs that belong to the same clade as other EXPA7 orthologs from angiosperms (Supplemental Figure 2 and Supplemental Data Set 2).…”
Section: The Function Of Rsl4 Is Conserved In the Tracheophyte Lineagementioning
confidence: 99%
“…During the last three decades, cucumber transformation techniques have undergone advances. The most effective method to transfer the desired genes into the cucumber genome is to use an Agrobacterium-mediated transformation approach (Trulson et al, 1986;Kose and Koç, 2003;Lin et al, 2011a). However, the genotype dependency, lowregeneration efficiency, and low reproducibility of this transformation system limit the use of transformation techniques in the genetic improvement of cucumber.…”
Section: Introductionmentioning
confidence: 99%